(untitled) (Al-Qamar, 2018)
Muhammad Aslam Sheikhūpūrī was a well-known religious scholar, who wrote several books in different fields of Islamic sciences and delivered talks on various religious subjects. In the field of Qur’ānic commentary, his effort named "Tashīl al-Bayān” is a very important and significant work. This article introduces Sheikhūpūrī’s important works and presents a research study of his referred commentary of the Quran. This demonstrates that the commentator has done a valuable work in the field. His commentary can be said a worthwhile addition in the area of exegetical literature.